Immunological characterization of the complement regulator factor H-binding CRASP and Erp proteins of Borrelia burgdorferi - Kraiczy, Peter; Hartmann, Kristina; Hellwage, Jens; Skerka, Christine; Kirschfink, Michael; Brade, Volker; Zipfel, Peter F.; Wallich, Reinhard; Stevenson, Brian (International journal of medical microbiology, 2005)
Complement activation plays an important role in the elimination of invading microorganisms. Borrelia (B.) burgdorferi sensu lato the etiological agent of Lyme borreliosis, can resist complement-mediated killing. The mechanism of complement resistance of B. burgdorferi sensu stricto apparently depends on the expression of several outer surface proteins described as CRASPs (complement regulator-acquiring surface proteins). These borrelial surface proteins are able to bind components of the complement regulatory system, factor H and/or factor H-like protein 1 (FHL-1), two crucial fluid-phase negative regulators of the alternative pathway of complement. It was previously demonstrated that one CRASP is encoded by a member of the erp gene family. The purpose of the study was to use a set of monoclonal antibodies (mAb) and polyclonal antisera to characterize the relatedness of factor H-binding CRASP and Erp proteins among several B. burgdorferi sensu stricto and B. afzelii strains. Based on the observed cross-reactivities between B. burgdorferi sensu stricto strains LW2 and PKa-1, it is concluded that BbCRASP-3 is similar to ErpP, BbCRASP-4 is structurally related to ErpC, and BbCRASP-5 is similar to ErpA. The BaCRASP-2 and BaCRASP-4 proteins of B. afzelii strain EB1 reacted with both anti-ErpA and anti-ErpP antibodies whereas BaCRASP-5 of B. afzelii strain FEM1-D15 exclusively reacted with BbCRASP-3/ErpP specific antibodies. Together, these data indicate that most of the factor H-binding CRASPs are members of the Erp protein family, which represents a polymorphic class of proteins with similar or identical immunological reactivities.
Available online 24 August 2005
Gesehen am 22.02.2021